Students’ systems thinking while modeling a dynamic ecological system - Lankers, Annika; Timm, Justin; Schmiemann, Philipp (Frontiers in Education, 2023)
The world is facing global ecological changes, making it essential to prepare the future generation with the necessary understanding to effectively navigate and address complex tasks. Previous research has shown that both systems thinking and scientific modeling are particularly relevant in investigating the comprehensive understanding of such complex phenomena. However, there has been little research on the interrelation between systems thinking and scientific modeling. To address this research gap, we conducted a thinking-aloud study with nine high school students by confronting them with a simulation of a dynamic ecological system. Our qualitative content analysis of the students’ statements indicates an interrelation between systems thinking and scientific modeling. The students frequently show systems thinking during the exploration, whereas when developing a graphical model, the students are primarily involved in identifying the system organization and analyzing the system behavior. When predicting future system states, students engage in modeling the system evolution. Furthermore, during verbalizing analogies and experiences, students refer to the system organization and behavior, whereas in mental modeling, students additionally model the system evolution. These results illustrate a central difference between the two perspectives. Thus, scientific modeling focuses on students’ activities during their understanding process, while systems thinking addresses students’ analysis of systems and their properties. While the phenomenon exploration may not require systems thinking, pattern recognition and model development are frequently associated with identifying the system organization and analyzing the system behavior. Systems thinking must also be applied when deriving possible future system states by modeling the system evolution, an activity that is closely related to the prediction phase of scientific modeling. Interestingly, in our study, the students also demonstrated the modeling of system evolution in their mental modeling. In conclusion, a complementary consideration of systems thinking and scientific modeling affords a deeper understanding of students’ cognitive processes in dealing with complex phenomena.